1991
DOI: 10.5006/1.3585194
|View full text |Cite
|
Sign up to set email alerts
|

Intergranular Cracking of Ni-16Cr-9Fe Alloys in High Temperature Water

Abstract: Al 7075 alloys since the oxalic ions enhance separation between the pitting and corrosion potentials, whereas the nitrate ions appreciably increase the corrosion potential. Thus the combination of the two ions results not only in separation of the two potentials, but also to an appreciable positive shift of the pitting potential. The immersion test experiments showed a preferential dissolution of the Zn contained in the alloy in the presence of nitrate ions. ABSTRACTThe objective of this work is to provide a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 3 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…Was and coworkers [20][21][22][23][24][25][26] and Vaillant,et al,13 reported a correlation between the occurrence of IG-SCC in hydrogenated high-temperature water/steam conditions and creep behavior for nickel-based alloys with various carbon and chromium concentrations. Regarding the mechanism of IGSCC of austenitic SS, Arioka, et al, 2 reported that GB sliding might play an important role by itself or in conjunction with other reactions such as crack tip dissolution, based upon closer observations of the initiation of IGSCC after CERT testing in hydrogenated environments and a comparison with surfaces produced in creep testing.…”
Section: Role Of Grain Boundary Sliding On the Intergranular Stress Cmentioning
confidence: 99%
“…Was and coworkers [20][21][22][23][24][25][26] and Vaillant,et al,13 reported a correlation between the occurrence of IG-SCC in hydrogenated high-temperature water/steam conditions and creep behavior for nickel-based alloys with various carbon and chromium concentrations. Regarding the mechanism of IGSCC of austenitic SS, Arioka, et al, 2 reported that GB sliding might play an important role by itself or in conjunction with other reactions such as crack tip dissolution, based upon closer observations of the initiation of IGSCC after CERT testing in hydrogenated environments and a comparison with surfaces produced in creep testing.…”
Section: Role Of Grain Boundary Sliding On the Intergranular Stress Cmentioning
confidence: 99%
“…Other researchers [25][26][27][28][29] performed detailed analyses of crack tips using analytical transmission electron microscopy (ATEM) to characterize the mechanism of IGSCC in nonsensitized Type 304 in BWR environments and of CW316 in PWR environments. Furthermore, Was and coworkers [30][31][32][33][34][35][36] and Vaillant, et al, 37 studied the role of GB sliding on IGSCC of nickel-based alloys in PWR environments. They confi rmed some evidence of GB sliding after constant extension rate testing (CERT) in a mixed gas atmosphere of argon and hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Was and his co-workers (8)(9)(10) performed a systematic study on the effect of P and other trace elements (C and B) on the microstructure, intergranular stress corrosion cracking, and creep resistance of Ni-Cr-Fe alloy 600. It was revealed that the addition of P to Ni-Cr-Fe alloy 600 improved the intergranular cracking resistance and creep resistance in Ar or high temperature water.…”
Section: Introductionmentioning
confidence: 99%